Noël – Christmas: “Joyeux Noël” “Merry Christmas” / Seng Hui Zanne - Seng, Hui Zanne (Academy of Language Studies, 2024)
This is a greeting used generally during Christmas. The French celebrate Christmas on the 25th of December, one of France's important holidays. The Christmas season usually begins on the 1st of December and lasts until the 6th of January, Three Kings Day (L'Épiphanie). A king cake (Galette des Rois) is always associated with celebrating L'Épiphanie. During Christmas, the French people can enjoy shopping in Christmas markets, particularly a big Christmas market in Les Champs-Elysées. Even in a small town, you can also find Christmas markets there. French people usually have a Christmas meal on the 24th of December, Christmas Eve or le Réveillon de Noël in French. After Christmas Eve, the most exciting moment for kids is waiting for the gifts. For kids to receive a gift in France, shoes must be left in front of the fireplace, near the windows or the Christmas tree, instead of hanging stockings by the fireplace. French kids believe Father Christmas (Père Noël) will fill the shoes with gifts.